Diethyl 2-(phenylcarbamoyl)phenyl phosphorothioates: synthesis, antimycobacterial activity and cholinesterase inhibition - Vinšová, Jarmila; Krátký, Martin; Komlóová, Markéta; Dadapeer, Echchukattula; Stěpánková, Sárka; Vorčáková, Katarína; Stolaříková, Jiřina (Molecules (Basel, Switzerland), 2014)
A new series of 27 diethyl 2-(phenylcarbamoyl)phenyl phosphorothioates (thiophosphates) was synthesized, characterized by NMR, IR and CHN analyses and evaluated against Mycobacterium tuberculosis H37Rv, Mycobacterium avium and two strains of Mycobacterium kansasii. The best activity against M. tuberculosis was found for O-{4-bromo-2-[(3,4-dichlorophenyl)carbamoyl]phenyl} O,O-diethyl phosphorothioate (minimum inhibitory concentration of 4 µM). The highest activity against nontuberculous mycobacteria was exhibited by O-(5-chloro-2-{[4-(trifluoromethyl)phenyl]carbamoyl}-phenyl) O,O-diethyl phosphorothioate with MIC values from 16 µM. Prepared thiophosphates were also evaluated against acetylcholinesterase from electric eel and butyrylcholinesterase from equine serum. Their inhibitory activity was compared to that of the known cholinesterases inhibitors galanthamine and rivastigmine. All tested compounds showed a higher (for AChE inhibition) and comparable (for BChE inhibition) activity to that of rivastigmine, with IC50s within the 8.04 to 20.2 µM range.
Keywords: Mycobacterium kansasii; cholinesterasové inhibitory; Microbial Sensitivity Tests; Acetylcholinesterase; mikrobiální testy citlivosti; Mycobacterium avium; Antitubercular Agents; antituberkulotika; acetylcholinesterasa; Cholinesterase Inhibitors